2016
DOI: 10.1038/srep22197
|View full text |Cite
|
Sign up to set email alerts
|

Statins Improve Long Term Patency of Arteriovenous Fistula for Hemodialysis

Abstract: The protective effects of statins against stenosis for permanent hemodialysis access have been repeatedly demonstrated in animal studies, but remain controversial in human studies. This study aims to evaluate the association between statin use and permanent hemodialysis access patency using a nationwide hemodialysis cohort. A total of 9862 pairs of statin users and non-users, matched by age and gender, were selected for investigation from 75404 new hemodialysis patients during 2000–2008. The effect of statins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…The presence of multiple risk factors may dictate the construction of an alternative access; however, in the absence of randomised trials, the level of evidence would be low and grade of recommendation weak. In view of the association between dyslipidaemia and primary and primary assisted patency, and the controversial effect of statins, 22,23 recommendation grade for statin use would also be weak. Nevertheless, functionality rates also affect the cost effectiveness of the procedure and should be taken into account during pre-operative planning, 24 while similar recommendations may be applicable for patients with poor FSP rates, for example less than 25% at 1 year, at the additional cost of multiple maintenance angioplasty and/or thrombectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple risk factors may dictate the construction of an alternative access; however, in the absence of randomised trials, the level of evidence would be low and grade of recommendation weak. In view of the association between dyslipidaemia and primary and primary assisted patency, and the controversial effect of statins, 22,23 recommendation grade for statin use would also be weak. Nevertheless, functionality rates also affect the cost effectiveness of the procedure and should be taken into account during pre-operative planning, 24 while similar recommendations may be applicable for patients with poor FSP rates, for example less than 25% at 1 year, at the additional cost of multiple maintenance angioplasty and/or thrombectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…304 Statins have pleiotropic beneficial actions besides lipid lowering but non-randomised studies and nationwide cohort analysis report contradictory results regarding their effects on VA patency rates. 314,315 As previously described, most recommendations are based on clinical experience, but interventions that clearly improve VA maturation and suitability for HD are needed. 164…”
Section: C 284mentioning
confidence: 99%
“…Patients administered warfarin showed worse primary graft patency (RR, 1.33; P = 0.037). Statin treatment could be associated with reduced neointimal proliferation, vascular inflammation, and improved AVF dysfunction [137][138][139]. A Cochrane review reported that antiplatelet treatment can improve the 1-month patency rates of AVFs and AVGs [140].…”
Section: Quality Assurance Processmentioning
confidence: 99%